In vitro activity of encapsulated lactic acid bacteria on aflatoxin production and growth of Aspergillus Spp. Issue 3 (19th January 2021) - mohammadi, Rouhollah; Abbaszadeh, Sepideh; Sharifzadeh, Aghil; Sepandi, Mojtaba; Taghdir, Maryam; Youseftabar Miri, Najmeh; Parastouei, Karim
Abstract: This study aimed to investigate the potential ability of simultaneously used L. acidophilus(LA‐5), L.rhamnosus(LGG), and L.casei(LC‐01) in encapsulated (E) and nonencapsulated (NE) forms in mycelial growth of Aspergillus spp and aflatoxin production by A. flavus . In order to assess the zone of fungal growth inhibition by E and NE lactic acid bacteria, the agar well diffusion method was applied. Quantification of aflatoxin was performed using a high‐performance liquid chromatography technique. Lactic acid bacteria exhibited high antifungal activity and significantly reduced AFB1, AFB2, AFG1, and AFG2 production in both E and NE forms compared to the control group. The percentage of reduction in total AFs production in treated samples with E and NE lactic acid bacteria was 94.1% and 95.5%, respectively. These results suggested that simultaneously used lactic acid bacteria in E and NE forms can prevent growth and decrease aflatoxin production of toxigenic aspergilla. Abstract : This study showed that Lactic acid bacteria exhibited antifungal activity and significantly reduced AFB1, AFB2, AFG1, and AFG2 production in both encapsulated and nonencapsulated forms compared to the control group. The results of this study suggested that simultaneously used lactic acid bacteria in E and NE forms can prevent growth and decrease aflatoxin production of toxigenic aspergilla.